CHRODIS criteria applied to the MASK (MACVIA‐ARIA Sentinel NetworK) Good Practice in allergic rhinitis: a SUNFRAIL report. Issue 1 (23rd October 2017) - Bousquet, J.; Onorato, G. L.; Bachert, C.; Barbolini, M.; Bedbrook, A.; Bjermer, L.; de Sousa, J. Correia; Chavannes, N. H.; Cruz, A. A.; De Manuel Keenoy, E.; Devillier, P.; Fonseca, J.; et al.
Abstract: A Good Practice is a practice that works well, produces good results, and is recommended as a model. MACVIA‐ARIA Sentinel Network (MASK), the new Allergic Rhinitis and its Impact on Asthma (ARIA) initiative, is an example of a Good Practice focusing on the implementation of multi‐sectoral care pathways using emerging technologies with real life data in rhinitis and asthma multi‐morbidity. The European Union Joint Action on Chronic Diseases and Promoting Healthy Ageing across the Life Cycle (JA‐CHRODIS) has developed a checklist of 28 items for the evaluation of Good Practices. SUNFRAIL (Reference Sites Network for Prevention and Care of Frailty and Chronic Conditions in community dwelling persons of EU Countries), a European Union project, assessed whether MASK is in line with the 28 items of JA‐CHRODIS. A short summary was proposed for each item and 18 experts, all members of ARIA and SUNFRAIL from 12 countries, assessed the 28 items using a Survey Monkey‐based questionnaire. A visual analogue scale (VAS) from 0 (strongly disagree) to 100 (strongly agree) was used. Agreement equal or over 75% was observed for 14 items (50%). MASK is following the JA‐CHRODIS recommendations for the evaluation of Good Practices.